Comparative Evaluation of the Performance of LQR and LQT Methods in Limited Actualized Mechanical System Control for Technology Empowerment in Local Communities - Naufal Rendra Saputra (Maritime in Community Service and Empowerment, 2023)
This study compares the performance of the Linear Quadratic Regulator (LQR) and Linear Quadratic Tracking (LQT) methods in controlling a limited oscillatory mechanical system, with a focus on their potential applications in community-based technology empowerment programs. The comparison was conducted using numerical simulation techniques, with key performance indicators such as mean squared error (MSE) and convergence time. The results show that the LQR method outperforms LQT in controlling the oscillatory system with more consistent accuracy and faster convergence. However, LQT demonstrates superior flexibility and robustness in handling more complex scenarios and unexpected perturbations. These characteristics make LQT particularly suitable for applications in dynamic environments, such as those found in local industries or community-driven projects. The choice of method ultimately depends on the specific requirements and conditions of the system being controlled. This research contributes to community development by exploring efficient control strategies that can improve local industrial systems, leading to better energy utilization and productivity, which in turn supports sustainable economic growth within the community.